The Lebanese expatriation: Between return and connection - Omar, Maha Haj; Nehme, Mohamad; Mohtar, Lojeen Al (Edelweiss Applied Science and Technology, 2025)
Migration flows, particularly those involving skilled labor and capital, have profound effects on both the countries of origin and destination. Lebanon, a developing economy plagued by persistent security and financial crises, has experienced significant migration waves in recent decades. These large-scale emigrations have led to various positive and negative economic and social transformations. While most previous studies have focused on the adverse effects of Lebanon’s brain drain and capital outflow, this study emphasizes the crucial role of Lebanese expatriates in supporting their families and revitalizing certain economic sectors. Through a mixed-methods approach, this study examines the factors that prevent Lebanese expatriates from returning to their homeland by analyzing data from 225 participants. Using quantitative methods, including regression and Chi-Square analysis on the SPSS platform, the findings reveal that despite their relatively limited impact, Lebanese expatriates contribute positively to the local economy and provide financial support to their families. The study also highlights that unemployment is a primary driver of emigration, with government reforms, job opportunities, and political stability identified as key factors influencing the decision to return.